2021
DOI: 10.1088/1755-1315/779/1/012112
|View full text |Cite
|
Sign up to set email alerts
|

Household composting in North Syria case study

Abstract: The purpose of this study (Technical Assessment) is to recognize how to convert solid waste materials into composting in North Syria, Non-State Armed Group (NSAG) controlled areas, and indicates the produced mass of the compost per capita, the assessment showed that: the weather condition in the north of Syria is suitable for converting the domestic solid waste into compost within 99-111 days at the temperature: 10-350C, The volume of the compost is about: 49.3%-55.2% of the volume of the solid waste before co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The same condition also occurs in Syria, where based on research the people there do not know how to process household waste into compost. Composting household waste in addition to reducing the volume of waste also saves the cost of collecting, moving, and disposing of solid waste (Saghir, 2021). The special case for waste management among Indonesians is hampered by the lack of public understanding of waste management (Susilo et al, 2021).…”
Section: Composting Of Household Wastementioning
confidence: 99%
“…The same condition also occurs in Syria, where based on research the people there do not know how to process household waste into compost. Composting household waste in addition to reducing the volume of waste also saves the cost of collecting, moving, and disposing of solid waste (Saghir, 2021). The special case for waste management among Indonesians is hampered by the lack of public understanding of waste management (Susilo et al, 2021).…”
Section: Composting Of Household Wastementioning
confidence: 99%
“…In Syria, the management of municipal solid waste is a serious challenge facing both national and local authorities due to the destruction of infrastructure, damaging or looting of collection vehicles and waste containers, devastation of government institutions, displacement of residents into safe areas as a consequence of the 2011 conflict (Noufal et al, 2020). According to Saghir (2021), current solid waste management practices include the following:…”
Section: Biogenous Waste Management and Composting In The Mena Regionmentioning
confidence: 99%
“…In Syria, the management of municipal solid waste is a serious challenge facing both national and local authorities due to the destruction of infrastructure, damaging or looting of collection vehicles and waste containers, devastation of government institutions, displacement of residents into safe areas as a consequence of the 2011 conflict (Noufal et al, 2020). According to Saghir (2021), current solid waste management practices include the following: There is a lack of accurate data on the quantities of the waste generated, their types and characteristics or even the waste disposal needs of the populations. Interviews by Noufal et al (2020) were conducted with the staff of the municipal waste management department in Homs, who reported that, in 2018, an average of 600 tons of municipal solid waste was generated per day and an average daily amount of 0.65 kg per person, out of which 69.1% was composed of biogenous waste.…”
Section: Syriamentioning
confidence: 99%
See 2 more Smart Citations